A Simple Technique for the Corrosion Inhibition of Underwater Cannonball from a Shipwreck - Riyanto; Muhammad Malthuf Jazuli; Imam Sahroni; Muhammad Miqdam Musawwa; Nahar Cahyandaru; Endang Tri Wahyuni (International Journal of Technology, 2023)
This study aims to conserve the underwater cannonball before storing it in a museum. Removing the protective crust of iron artifacts without the correct and proper method can cause rapid corrosion. To prevent damage, artifacts must be conserved in the right solution. Conservation was conducted in four stages during this research project. The first stage is the identification of weathering, and the second stage is the analysis and characterization of the corroded surface using a microscope, XRD (X-ray diffraction), XRF (X-ray fluorescence), and SEM (scanning electron microscopy). The third stage is the passivation/deactivation process, achieved using sodium hydroxide, soapy water and kaffir lime water. The fourth stage is stabilizing/coating the iron cannonball underwater heritage materials as soon as possible using microcrystalline wax to prevent further corrosion. This stage should solve the conservation problems associated with the object so that the object can last for a long time. Dry and wet-activated corrosion was characterized by applying XRD to the obtained mineral akageneite. The akageneite minerals were actively corroded and contained high concentrations of Cl atoms revealing dry and wet activated corrosion of 66.60% and 64.96%, respectively. After being conserved with several steps and NaOH, soapy water and kaffir lime water, inactive corrosion was observed. Based on the results of the analysis performed with XRF, the cannonball does not contain Cl, and the Fe content is 98.99%. The conservation method used in this research is excellent and appropriate for conserving cultural heritage materials, including underwater iron cannonballs.